Beginning DotNetNuke 4.0 Website Creation in C# 2005 with Visual Web Developer 2005 Express From Novice to Professional - Symmonds, Nick.; SpringerLink (Online service) (Berkeley, CA : Apress, 2006)
Are you tasked with creating and maintaining a web presence? Do you suspect that there is a better way to manage business internally? Beginning DotNetNuke 4.0 Website Creation in C# 2005 with Visual Web Developer 2005 Express is for you. It leads you through the emerging world of web portals by applying the most user-friendly and current development software, like C# Express and the powerful, flexible DotNetNuke. You will learn to create the professional web presence your company needs. The book takes you through the steps necessary to get an internal web portal running for employee use. If you have some programming experience and creativity, this book will help you expand your business presence in a short amount of time. It features simple explanations and proof-of-concept examples throughout. The book concludes with the creation of a web portlet that you can plug into an external website for a web presence.
The Basics -- The Express and DotNetNuke Combination -- Installation -- Basic C# -- Visual Web Developer -- DotNetNuke Basics -- Creating a DNN Module -- Finishing the DotNetNuke Module -- DNN Permissions and Portals -- DNN Hosting -- Creating a DNN Skin -- JavaScript and Ajax -- Next Steps and Suggestions.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books